Coating for casting alloy steel evanescent mode as well as preparation method and application thereof
By using a cast alloy steel disappearing mold coating containing aggregate, high-temperature resistant and environmentally friendly adhesive and other components, the problems of low high temperature strength of the coating and harmful gas volatility in the prior art are solved, and the smooth surface of the casting and the casting quality are improved.
Patent Information
- Application Number
- CN202510076278.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-17
Smart Images

Figure BDA0005247185730000071 
Figure BDA0005247185730000072 
Figure BDA0005247185730000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lost foam coatings, in particular to a coating for lost foam casting of alloy steel and a preparation method and application thereof. Background Art
[0002] Lost foam casting is also known as gasification mold casting, full mold casting. The core technology is to use foam plastic (EPS, STMMA or EPMMA) polymer materials to replace the original wooden mold or metal mold, and use plastic sheet processing and bonding or plastic beads to foam to form a pattern (white mold) similar to the size and shape of the casting. After being dipped in refractory coating (for strengthening, smoothing and breathability) and dried, it is buried in dry quartz sand and shaped by three-dimensional vibration. After shaping, the pattern is not taken out, so as to establish a solid cavity with the pattern in the sand box. The molten metal liquid is cast under negative pressure, so that the polymer material model is heated and vaporized and extracted, and then replaced by liquid metal and cooled, and the desired casting is obtained after solidification.
[0003] Compared with traditional casting methods such as sand casting, lost foam casting has a series of advantages:
[0004] (1) Lost foam casting has a large degree of freedom in design. For parts with complex shapes, lost foam casting adopts the method of making multiple mold pieces and then gluing them together to obtain the overall shape. Finally, the overall casting is obtained by molding and pouring without the need for complex core molds and multi-component assembly, which greatly reduces the production cost and difficulty.
[0005] (2) Lost foam casting can achieve nearly zero-residue casting, and the material utilization rate can reach more than 95%, while the material utilization rate of traditional casting technology is usually low, generating a large amount of waste; the surface finish and dimensional accuracy of the castings produced by lost foam casting are higher, with fewer internal defects, reducing the workload of subsequent processing and cleaning.
[0006] (3) Lost foam casting can reduce or eliminate the manufacturing and maintenance costs of molds. At the same time, due to its one-time molding characteristics, it can shorten the production cycle and improve the production efficiency of the enterprise.
[0007] (4) The range of casting material selection is wide, and the lost foam casting method can be used to cast metal castings such as steel castings, iron castings, and aluminum-magnesium alloy castings.
[0008] Therefore, the lost foam casting technology is widely used in the automotive, aerospace and other industries. Also due to these characteristics, in the lost foam casting process, a layer of coating on the outside of the white mold has an important influence on the filling of the molten metal, the discharge of the decomposition products of the mold and the quality of the casting. The main function of the coating is actually to be used as a mold during casting. It should have high refractoriness and chemical stability, certain room temperature strength and rigidity to prevent sand sticking and box collapse; it has high air permeability to ensure the timely discharge of the gas or liquid products produced by the thermal decomposition of the mold; high high temperature strength and high temperature crack resistance can prevent the coating from collapsing under the scouring of high temperature fluids and back pressure (high temperature molten metal, white mold gasification products), and prevent the cracking of the coating from causing the molten metal to penetrate into the mold sand and cause the casting to stick to the sand. In order to ensure the quality of the coating, it should also have good suspension stability, good wettability and adsorption, and good coating and anti-dripping properties. Production experience points out that 60% of the reasons for the scrap of lost foam castings are attributed to the coating.
[0009] The quality of the coating can be equated with the quality of the final casting. The materials commonly used in the lost foam coatings on the market often contain some environmentally unfriendly raw materials, especially some commonly used organic adhesives, such as asphalt, coal tar, rosin, phenolic resin, etc. These raw materials will produce VOCs harmful gases such as benzene, toluene, styrene, ethylbenzene, etc. during sintering and high-temperature casting. The commonly used surfactant OP-10 may have an adverse effect on the environment, especially it is difficult to degrade in water bodies and has potential harm to aquatic organisms. Summary of the invention
[0010] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a coating for casting alloy steel lost foam and a preparation method and application thereof, which is used to solve the problems in the prior art of volatile harmful gases such as a large amount of VOCs volatilized during casting and the low high temperature strength of the coating leading to casting defects such as box collapse and sand sticking.
[0011] To achieve the above-mentioned object and other related objects, the present invention provides a coating for casting alloy steel lost foam, characterized in that it comprises the following raw materials in parts by weight: 79-89 parts of aggregate, 3-7 parts of binder, 4-7 parts of suspending agent, 1.5-3 parts of surfactant, 1.5-2.5 parts of defoamer and 1-1.5 parts of preservative;
[0012] The aggregate, in terms of mass percentage, comprises 78-82wt% bauxite, 12-15wt% mica and 3-10wt% quartz powder;
[0013] The binder comprises, by weight percentage, 42-50 wt% of anhydrous aluminum dihydrogen phosphate, 18-25 wt% of white carbon black, 12-17 wt% of ethylene glycol and 8-28 wt% of magnesium oxide.
[0014] The present invention also provides a method for preparing the coating for casting alloy steel lost foam as described above, comprising the following steps:
[0015] S1. Prepare sodium carboxymethyl cellulose suspension, sodium bentonite suspension and sodium alginate suspension according to the proportion of ingredients;
[0016] S2. Mix and grind the aggregate, anhydrous aluminum dihydrogen phosphate, white carbon black and magnesium oxide according to the proportion of ingredients to obtain a mixed abrasive;
[0017] S3, the three suspensions in step S1 are mixed to obtain a mixed suspension, the surfactant, defoamer, preservative and ethylene glycol are added to the mixed suspension in batches, and the obtained mixed solution is then added to the mixed abrasive obtained in step S2 in batches, and mixed evenly to obtain the coating for the lost foam of cast alloy steel.
[0018] The present invention also provides an application of the coating for casting alloy steel lost foam as described above in the field of alloy steel lost foam casting.
[0019] As described above, the coating, preparation method and application of the alloy steel lost foam casting of the present invention have the following beneficial effects:
[0020] The coating for casting alloy steel lost foam of the present invention uses a high-temperature resistant environmentally friendly binder aluminum dihydrogen phosphate, and adds nano-scale white carbon black and magnesium oxide, which are also high-temperature resistant environmentally friendly inorganic compounds, to increase the adhesion strength, and the surfactant uses a more environmentally friendly TO-9 instead of OP-10; the environmentally friendly coating of the present application can maintain strength during firing, and at the same time maintains good suspension, high-temperature air permeability, coating and hanging properties, high-temperature crack resistance and shedding properties of the coating, and the surface of the casting is smooth and free of sticky sand. DETAILED DESCRIPTION
[0021] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0022] When a numerical range is disclosed herein, the above range is deemed to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all sub-ranges included therein. For example, a specified range from "1 to 10" should be deemed to include any and all sub-ranges between a minimum of 1 and a maximum of 10. Exemplary sub-ranges of ranges 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, and the like.
[0023] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; and, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0024] The first aspect of the present invention provides a coating for casting alloy steel lost foam, comprising the following raw materials in parts by weight:
[0025] 79-89 parts, 79-81 parts, 81-83 parts, 83-85 parts, 85-87 parts or 87-89 parts of aggregate;
[0026] 3-7 parts, 3-4 parts, 4-5 parts, 5-6 parts or 6-7 parts of binder;
[0027] Suspension agent 4-7 parts, 4-5 parts, 5-6 parts or 6-7 parts;
[0028] 1.5-3 parts, 1.5-1.7 parts, 1.7-1.9 parts, 1.9-2.1 parts, 2.1-2.3 parts, 2.3-2.5 parts, 2.5-2.7 parts, 2.7-2.9 parts or 2.9-3.0 parts of surfactant;
[0029] 1.5-2.5 parts, 1.5-1.7 parts, 1.7-1.9 parts, 1.9-2.1 parts, 2.1-2.3 parts or 2.3-2.5 parts of defoaming agent;
[0030] 1-1.5 parts, 1-1.1 parts, 1.1-1.2 parts, 1.2-1.3 parts, 1.3-1.4 parts or 1.4-1.5 parts of preservatives;
[0031] Wherein, the aggregate, by mass percentage, comprises 78-82wt%, 78-79wt%, 79-80wt%, 80-81wt% or 80-82wt% bauxite, 12-15wt%, 12-13wt%, 13-14wt% or 14-15wt% mica and 3-10wt%, 3-4wt%, 4-5wt%, 5-6wt%, 6-7wt%, 7-8wt%, 8-9wt% or 9-10wt% quartz powder;
[0032] The binder includes, by mass percentage, 42-50wt%, 42-44wt%, 44-46wt%, 46-48wt% or 48-50wt% anhydrous aluminum dihydrogen phosphate, 18-25wt%, 18-20wt%, 20-22wt%, 22-24wt% or 24-25wt% white carbon black, 12-17wt%, 12-13wt%, 13-14wt%, 14-15wt%, 15-16wt% or 16-17wt% ethylene glycol and 8-28wt%, 8-10wt%, 10-14wt%, 14-18wt%, 18-20wt%, 20-24wt% or 24-38wt% magnesium oxide.
[0033] In some embodiments of the present invention, the suspending agent includes, by mass percentage, 35-50wt%, 35-40wt%, 40-45wt% or 45-50wt% sodium carboxymethyl cellulose, 45-50wt%, 45-46wt%, 46-47wt%, 47-48wt%, 48-49wt% or 49-50wt% sodium bentonite and 10-20wt%, 10-12wt%, 12-14wt%, 14-16wt%, 16-18wt% or 18-20wt% sodium alginate.
[0034] In some embodiments of the present invention, the surfactant is isomeric tridecanol polyoxyethylene ether (TO-9).
[0035] In some embodiments of the present invention, the defoaming agent is n-octanol.
[0036] In some embodiments of the present invention, the preservative, by mass percentage, includes 25-50wt%, 25-30wt%, 30-35wt%, 35-40wt%, 40-45wt% or 45-50wt% potassium sorbate and 50-75wt%, 50-55wt%, 55-60wt%, 60-65wt%, 65-70wt% or 70-75wt% chitosan.
[0037] In the present invention, aggregate is the main component of the coating, and is directly related to the generation of defects such as sand adhesion, pores, and slag inclusions in castings. The aggregate material in the present invention has the characteristics of high fire resistance, high air permeability, stable chemical properties, no wetting or reaction with molten metal, and is widely available, green and environmentally friendly, and low in price, which can reduce enterprise costs. Bauxite has stable chemical properties, high temperature resistance, is not easy to react with metals or metal oxides, and is not easily infiltrated by molten steel and other molten metals; mica has stable chemical properties, high temperature resistance, and corrosion resistance. Its internal structure is layered and has good elasticity. Adding it to the coating can improve the high-temperature air permeability, sintering strength and suspension of the coating; quartz sand has a wide range of sources and is low in price. At high temperatures, it undergoes phase change and increases in volume. Adding a small amount to the coating solution can improve the air permeability of the coating. Combining it with bauxite can reduce the sintering temperature and promote the sintering of the coating.
[0038] In the present invention, the main function of the binder is that it can bond the powder components of the coating, give the coating strength, resist the scouring of high-temperature metal liquid, support the sand mold, and prevent the coating from falling off or cracking. Aluminum dihydrogen phosphate is non-toxic and tasteless, high temperature resistant, and has high high-temperature bonding strength, but it also has defects such as high sintering temperature, large film shrinkage rate, and thus deformation and rupture of the adhesive film; nano-scale white carbon black is a white amorphous translucent solid colloidal nanoparticle, insoluble in water, with good permeability and dispersibility. In a water-based solution, a silanol group polycondensation reaction generates a silyl ether bond to improve the bonding strength and weaken the cracking tendency of the aluminum dihydrogen phosphate cured film. After combining with ethylene glycol, a condensation reaction occurs during sintering to generate a -SiO-O-SiO-bright coating film, which improves the brightness and strippability of the coating; ethylene glycol is a color transparent viscous liquid. As a chemical commonly used in the coating industry, ethylene glycol can greatly improve the dispersibility of the solute in the solution, improve the fluidity of the coating solution, and provide a certain moisturizing effect to prevent excessive shrinkage and cracking caused by too fast drying of the coating. Magnesium oxide is a white, odorless, non-toxic powder with extremely strong high temperature resistance. At room temperature, it can undergo a dehydration condensation cross-linking reaction with aluminum dihydrogen phosphate solution to produce a network of -O-Mg-O- bonds, so that the coating has a certain room / high temperature strength and reduces the thermal curing temperature of aluminum dihydrogen phosphate.
[0039] In the present invention, the main function of the suspending agent is to make each powder particle evenly suspended and dispersed in the carrier liquid, ensuring the formation of a uniform coating on the surface of the foam mold, and the suspending agent also gives the coating the required rheological properties. Sodium carboxymethyl cellulose is a linear polymer compound in the form of white fiber or powder, and its aqueous solution is pale white or transparent colloid, and has a certain suspension property; the main component of sodium bentonite is montmorillonite, which appears as white powder and has a fine scale layered structure, similar to sodium carboxymethyl cellulose. The combination of sodium carboxymethyl cellulose and sodium bentonite forms a stable network structure in aqueous solution and adsorbs solid particles of the coating, preventing solid particles from flocculating and falling, thereby improving the suspension of the coating liquid; sodium alginate is a by-product of extracting iodine and mannitol from kelp or seaweed. It appears as an odorless white or light yellow powder and is a natural polysaccharide that is highly soluble in water to form a colloid. The aqueous solution of sodium alginate can couple with bauxite, and the aluminum ions react with the carboxyl groups in the sodium alginate to form a coordination reaction. This coordination bonding causes the original sodium ions in the sodium alginate structure to be replaced by aluminum ions, which then combine to form a sodium alginate hydrogel with a three-dimensional network structure, thereby increasing the overall suspension of the coating liquid.
[0040] In the present invention, the surfactant can reduce the surface tension of the solvent, thereby enhancing the wettability of the water-based coating liquid to the surface of the hydrophobic EPS or EPMMA foam mold and improving the coating property. TO-9 is a low-biotoxic, easily degradable non-ionic surfactant, the main component of which is tridecanol polyoxyethylene ether, chemical formula C 13 H 27 O(CH2CH2O)9H is a colorless or light yellow liquid. Compared with alkylphenol polyoxyethylene ether surfactants such as OP-10, it has similar emulsification, wetting, and dispersing properties, but has lower biological toxicity and is more easily biodegradable.
[0041] In the present invention, the defoaming agent n-octanol is a transparent oily liquid with a citrus smell. During the production and stirring process of the coating, air enters the carrier liquid and is difficult to be discharged, thereby generating bubbles. When the coating is applied on the foam mold, the bubbles cannot be broken and flow down the surface defects during the sintering process. The defoaming agent can eliminate the foam in time when it is generated, ensuring that the coating surface is smooth.
[0042] In the present invention, the preservative can ensure that the coating can be stored for a long time without breeding microorganisms. In order to avoid the emergence of drug resistance or screening effect, the present invention uses two preservatives: potassium sorbitol and chitosan. Potassium sorbitol and chitosan are environmentally harmless preservatives.
[0043] In some embodiments of the present invention, the bauxite is 220-270 mesh, 220-230 mesh, 230-240 mesh, 240-250 mesh, 250-260 mesh or 260-270 mesh high alumina, and the Al2O3 content is greater than 85%.
[0044] In some embodiments of the present invention, the mica is 250-270 mesh, 250-260 mesh or 260-270 mesh.
[0045] In some embodiments of the present invention, the quartz powder is 180-220 mesh, 180-190 mesh, 190-200 mesh, 200-210 mesh or 210-220 mesh.
[0046] In some embodiments of the present invention, the white carbon black is nano-scale white carbon black.
[0047] In some embodiments of the present invention, the anhydrous aluminum dihydrogen phosphate, white carbon black, magnesium oxide, sodium carboxymethyl cellulose, sodium bentonite, sodium alginate, potassium sorbate and chitosan are all powders.
[0048] A second aspect of the present invention provides a method for preparing the coating for the lost foam of cast alloy steel as described above, comprising the following steps:
[0049] S1. Prepare sodium carboxymethyl cellulose suspension, sodium bentonite suspension and sodium alginate suspension according to the proportion of ingredients;
[0050] S2. Mix and grind the aggregate, anhydrous aluminum dihydrogen phosphate, white carbon black and magnesium oxide according to the proportion of ingredients to obtain a mixed abrasive;
[0051] S3, the three suspensions in step S1 are mixed to obtain a mixed suspension, the surfactant, defoamer, preservative and ethylene glycol are added to the mixed suspension in batches, and the obtained mixed solution is then added to the mixed abrasive obtained in step S2 in batches, and mixed evenly to obtain the coating for the lost foam of cast alloy steel.
[0052] In some embodiments of the present invention, the concentration of the sodium carboxymethyl cellulose suspension in step S1 is 2-3 wt%, for example, 2-2.2 wt%, 2.2-2.4 wt%, 2.4-2.6 wt%, 2.6-2.8 wt% or 2.8-3 wt%.
[0053] In some embodiments of the present invention, the concentration of the sodium bentonite suspension in step S1 is 1.5-2 wt%, for example, 1.5-1.6 wt%, 1.6-1.7 wt%, 1.7-1.8 wt%, 1.7-1.9 wt% or 1.9-2 wt%.
[0054] In some embodiments of the present invention, the concentration of the sodium alginate suspension in step S1 is 1-1.5 wt%, for example, 1-1.1 wt%, 1.1-1.2 wt%, 1.2-1.3 wt%, 1.3-1.4 wt% or 1.4-1.5 wt%.
[0055] Wherein, the solvents of the sodium carboxymethyl cellulose suspension, the sodium bentonite suspension and the sodium alginate suspension in step S1 are all deionized water.
[0056] The preparation of the sodium carboxymethyl cellulose suspension, the sodium bentonite suspension and the sodium alginate suspension in step S1 specifically includes adding sodium carboxymethyl cellulose, sodium bentonite and sodium alginate into deionized water, mixing them into slurries and foaming them. The foaming time is ≥20h. For example, 21h, 22h, 23h, 24h or ≥25h, etc.
[0057] In some embodiments of the present invention, the bauxite, mica and quartz powder in the aggregate in step S2 are kept at 200-230°C, 200-210°C, 210-220°C or 220-230°C for at least 30 minutes before mixing, and then cooled in a dry environment before mixing and grinding. The treated aggregate has higher air permeability and adsorption, and can form a more stable coating layer.
[0058] Wherein, the heat preservation is carried out in a high-temperature sintering furnace.
[0059] In some embodiments of the present invention, the grinding in step S2 is carried out in a planetary ball mill, using zirconium oxide grinding balls with a diameter of 1.4-1.6 mm, 1.4-1.5 mm or 1.5-1.6 mm and a content of more than 90%, and grinding the mixed abrasive at a rotation speed of 300-330 rpm, 300-310 rpm, 310-320 rpm or 320-330 rpm for 3-4 h, 3-3.5 h or 3.5-4 h.
[0060] A third aspect of the present invention provides an application of the coating for lost foam casting of alloy steel as described above in the field of lost foam casting of alloy steel.
[0061] Example 1
[0062] A coating for casting alloy steel lost foam, comprising the raw materials in parts by weight as shown in Table 1 below:
[0063] Table 1
[0064]
[0065] A method for preparing a coating for casting alloy steel lost foam, taking the above-mentioned weight portion of 10 kg as an example, comprises the following steps:
[0066] S1. Weigh 315 g of sodium carboxymethyl cellulose, 315 g of sodium bentonite powder, and 70 g of sodium alginate, add sufficient deionized water to each of them, use an electric stirrer to quickly stir into a slurry, and soak for 24 hours to obtain 10.5 kg of 3 wt% sodium carboxymethyl cellulose suspension, 15.8 kg of 2 wt% sodium bentonite suspension, and 7 kg of 1 wt% sodium alginate suspension for later use;
[0067] S2, 6400g of bauxite, 1200g of mica, 400g of quartz powder, 315g of anhydrous aluminum dihydrogen phosphate powder, 175g of nano-scale white carbon powder and 105g of magnesium oxide powder are put into a planetary ball mill, and zirconium oxide grinding balls with a diameter of 1.4-1.6mm and a content of more than 90% are selected, and the speed is set to 300 rpm to grind the mixed abrasive for 4h, wherein the bauxite, mica and quartz powder are first kept at 200°C in a high-temperature sintering furnace for 30-40min before mixing, and then cooled in a dry environment and put into the planetary ball mill;
[0068] S3, the three suspensions in step S1 are mixed and 300 g of TO-9, 200 g of n-octanol, 50 g of potassium sorbate, 50 g of chitosan, and 105 g of ethylene glycol are sequentially added to the mixture in small amounts and multiple times, and the obtained mixture is added to the mixed abrasive in step S2 in small amounts and multiple times, and stirred for 1.5 h using an electronic stirrer to obtain the desired coating;
[0069] S4. Fill the obtained paint into barrels and store them at room temperature away from light.
[0070] Example 2
[0071] A coating for casting alloy steel lost foam, comprising the following raw materials in parts by weight as shown in Table 2:
[0072] Table 2
[0073]
[0074]
[0075] A method for preparing a coating for casting alloy steel lost foam, taking the above-mentioned weight portion of 10 kg as an example, comprises the following steps:
[0076] S1. Weigh 225 g of sodium carboxymethyl cellulose, 225 g of sodium bentonite powder and 50 g of sodium alginate, add sufficient deionized water to each, use an electric stirrer to quickly stir into a slurry and soak for 24 h to obtain 7.5 kg of a 3 wt % sodium carboxymethyl cellulose suspension, 11.3 kg of a 2 wt % sodium bentonite suspension, and 5 kg of a 1 wt % sodium alginate suspension for later use;
[0077] S2, 6800g of bauxite, 1300g of mica, 400g of quartz powder, 225g of anhydrous aluminum dihydrogen phosphate powder, 125g of nano-scale white carbon powder and 75g of magnesium oxide powder are put into a planetary ball mill, and zirconium oxide grinding balls with a diameter of 1.4-1.6mm and a content of more than 90% are selected, and the speed is set to 300 rpm to grind the mixed abrasive for 4h, wherein the bauxite, mica and quartz powder are first kept at 200°C in a high-temperature sintering furnace for 30-40min before mixing, and then cooled in a dry environment and put into the planetary ball mill;
[0078] S3, the three suspensions in step S1 are mixed and 200 g of TO-9, 200 g of n-octanol, 50 g of potassium sorbate, 50 g of chitosan, and 75 g of ethylene glycol are added to the mixture in small amounts and multiple times, and the obtained mixture is added to the mixed abrasive in step S2 in small amounts and multiple times, and stirred for 1.5 h using an electronic stirrer to obtain the desired coating;
[0079] S4. Fill the obtained paint into barrels and store them at room temperature away from light.
[0080] Example 3
[0081] A coating for casting alloy steel lost foam, comprising the following raw materials in parts by weight as shown in Table 3:
[0082] Table 3
[0083]
[0084]
[0085] A method for preparing a coating for casting alloy steel lost foam, taking the above-mentioned weight portion of 10 kg as an example, comprises the following steps:
[0086] S1. Weigh 180 g of sodium carboxymethyl cellulose, 180 g of sodium bentonite powder and 40 g of sodium alginate, add sufficient deionized water to each, use an electric stirrer to quickly stir into a slurry and soak for 24 hours to obtain 6 kg of 3 wt% sodium carboxymethyl cellulose suspension, 9 kg of 2 wt% sodium bentonite suspension, and 4 kg of 1 wt% sodium alginate suspension for standby use;
[0087] S2, 7100g of bauxite, 1350g of mica, 450g of quartz powder, 135g of anhydrous aluminum dihydrogen phosphate powder, 75g of nano-scale white carbon powder and 45g of magnesium oxide powder were put into a planetary ball mill, and zirconium oxide grinding balls with a diameter of 1.4-1.6mm and a content of more than 90% were selected. The speed was set to 300 rpm to grind the mixed abrasive for 4h, wherein the bauxite, mica and quartz powder were first kept at 200°C in a high-temperature sintering furnace for 30-40min before mixing, and then cooled in a dry environment and put into the planetary ball mill;
[0088] S3, mix the two suspensions in S1 and add 150g TO-9, 150g n-octanol, 50g potassium sorbate, 50g chitosan and 45g ethylene glycol to the mixture in small amounts and several times, add the obtained mixture to the abrasive in S2 in small amounts and several times, stir with an electronic stirrer for 1.5h to obtain the desired coating;
[0089] S4. Fill the obtained paint into barrels and store them at room temperature away from light.
[0090] Comparative Example 1
[0091] A coating for casting alloy steel lost foam, comprising the following raw materials in parts by weight as shown in Table 4:
[0092] Table 4
[0093]
[0094] A method for preparing a coating for casting alloy steel lost foam, taking the above-mentioned weight portion of 10 kg as an example, comprises the following steps:
[0095] S1. Weigh 315 g of sodium carboxymethyl cellulose, 315 g of sodium bentonite powder, and 70 g of sodium alginate, add sufficient deionized water to each of them, use an electric stirrer to quickly stir into a slurry, and soak for 24 hours to obtain 10.5 kg of 3 wt% sodium carboxymethyl cellulose suspension, 15.8 kg of 2 wt% sodium bentonite suspension, and 7 kg of 1 wt% sodium alginate suspension for later use;
[0096] S2, put 7530g of bauxite, 470g of quartz powder, 315g of anhydrous aluminum dihydrogen phosphate powder, 175g of nano-scale white carbon powder and 105g of magnesium oxide powder into a planetary ball mill, select zirconium oxide grinding balls with a diameter of 1.4-1.6mm and a content of more than 90%, set the speed to 300 rpm to grind the mixed abrasive for 4h, wherein the bauxite and quartz powder are kept at 200°C in a high-temperature sintering furnace for 30-40min before mixing, and then cooled in a dry environment and put into the planetary ball mill;
[0097] S3, the three suspensions in step S1 are mixed and 300 g of TO-9, 200 g of n-octanol, 50 g of potassium sorbate, 50 g of chitosan, and 105 g of ethylene glycol are sequentially added to the mixture in small amounts and multiple times, and the obtained mixture is added to the mixed abrasive in step S2 in small amounts and multiple times, and stirred for 1.5 h using an electronic stirrer to obtain the desired coating;
[0098] S4. Fill the obtained paint into barrels and store them at room temperature away from light.
[0099] Comparative Example 2
[0100] A coating for casting alloy steel lost foam, comprising the following raw materials in parts by weight as shown in Table 5:
[0101] Table 5
[0102]
[0103] A method for preparing a coating for casting alloy steel lost foam, taking the above-mentioned weight portion of 10 kg as an example, comprises the following steps:
[0104] S1. Weigh 315 g of sodium carboxymethyl cellulose, 315 g of sodium bentonite powder, and 70 g of sodium alginate, add sufficient deionized water to each of them, use an electric stirrer to quickly stir into a slurry, and soak for 24 hours to obtain 10.5 kg of 3 wt% sodium carboxymethyl cellulose suspension, 15.8 kg of 2 wt% sodium bentonite suspension, and 7 kg of 1 wt% sodium alginate suspension for later use;
[0105] S2, 6740g of bauxite, 1260g of mica, 315g of anhydrous aluminum dihydrogen phosphate powder, 175g of nano-scale white carbon powder and 105g of magnesium oxide powder are put into a planetary ball mill, and zirconium oxide grinding balls with a diameter of 1.4-1.6mm and a content of more than 90% are selected, and the speed is set to 300 rpm to grind the mixed abrasive for 4h, wherein the bauxite and mica are first kept at 200°C in a high-temperature sintering furnace for 30-40min before mixing, and then cooled in a dry environment and put into the planetary ball mill;;
[0106] S3, the three suspensions in step S1 are mixed and 300 g of TO-9, 200 g of n-octanol, 50 g of potassium sorbate, 50 g of chitosan, and 105 g of ethylene glycol are sequentially added to the mixture in small amounts and multiple times, and the obtained mixture is added to the mixed abrasive in step S2 in small amounts and multiple times, and stirred for 1.5 h using an electronic stirrer to obtain the desired coating;
[0107] S4. Fill the obtained paint into barrels and store them at room temperature away from light.
[0108] Comparative Example 3
[0109] A coating for casting alloy steel lost foam, comprising the following raw materials in parts by weight as shown in Table 6:
[0110] Table 6
[0111]
[0112] A method for preparing a coating for casting alloy steel lost foam, taking the above-mentioned weight portion of 10 kg as an example, comprises the following steps:
[0113] S1. Weigh 315 g of sodium carboxymethyl cellulose, 315 g of sodium bentonite powder, and 70 g of sodium alginate, add sufficient deionized water to each of them, use an electric stirrer to quickly stir into a slurry, and soak for 24 hours to obtain 10.5 kg of 3 wt% sodium carboxymethyl cellulose suspension, 15.8 kg of 2 wt% sodium bentonite suspension, and 7 kg of 1 wt% sodium alginate suspension for later use;
[0114] S2, 6400g of bauxite, 1200g of mica, 400g of quartz powder, 371g of anhydrous aluminum dihydrogen phosphate powder, and 206g of nano-white carbon black are put into a planetary ball mill, and zirconium oxide grinding balls with a diameter of 1.4-1.6mm and a content of more than 90% are selected, and the speed is set to 300 rpm to grind the mixed abrasive for 4h, wherein the bauxite, mica and quartz powder are first kept at 200°C in a high-temperature sintering furnace for 30-40min before mixing, and then cooled in a dry environment and put into the planetary ball mill;
[0115] S3, the three suspensions in step S1 are mixed and 300 g of TO-9, 200 g of n-octanol, 50 g of potassium sorbate, 50 g of chitosan, and 123 g of ethylene glycol are sequentially added to the mixture in small amounts and multiple times, and the obtained mixture is added to the mixed abrasive in step S2 in small amounts and multiple times, and stirred for 1.5 h using an electronic stirrer to obtain the desired coating;
[0116] S4. Fill the obtained paint into barrels and store them at room temperature away from light.
[0117] Comparative Example 4
[0118] A coating for casting alloy steel lost foam, comprising the following raw materials in parts by weight as shown in Table 7:
[0119] Table 7
[0120]
[0121] A method for preparing a coating for casting alloy steel lost foam, taking the above-mentioned weight portion of 10 kg as an example, comprises the following steps:
[0122] S1. Weigh 315 g of sodium carboxymethyl cellulose, 315 g of sodium bentonite powder, and 70 g of sodium alginate, add sufficient deionized water to each of them, use an electric stirrer to quickly stir into a slurry, and soak for 24 hours to obtain 10.5 kg of 3 wt% sodium carboxymethyl cellulose suspension, 15.8 kg of 2 wt% sodium bentonite suspension, and 7 kg of 1 wt% sodium alginate suspension for later use;
[0123] S2, 6400g of bauxite, 1200g of mica, 400g of quartz powder, 420g of anhydrous aluminum dihydrogen phosphate powder and 140g of magnesium oxide powder are put into a planetary ball mill, and zirconium oxide grinding balls with a diameter of 1.4-1.6mm and a content of more than 90% are selected, and the speed is set to 300 rpm to grind the mixed abrasive for 4h, wherein the bauxite, mica and quartz powder are first kept at 200°C in a high-temperature sintering furnace for 30-40min before mixing, and then cooled in a dry environment and put into the planetary ball mill;
[0124] S3, the three suspensions in step S1 are mixed and 300 g of TO-9, 200 g of n-octanol, 50 g of potassium sorbate, 50 g of chitosan, and 140 g of ethylene glycol are added to the mixture in small amounts and multiple times, and the obtained mixture is added to the mixed abrasive in step S2 in small amounts and multiple times, and stirred for 1.5 h using an electronic stirrer to obtain the desired coating;
[0125] S4. Fill the obtained paint into barrels and store them at room temperature away from light.
[0126] The coatings prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 8 below.
[0127] Among them, the detection method is as follows:
[0128] Suspension rate: stoppered measuring cylinder sedimentation method, extract more than 100ml of the paint, shake it vigorously for more than 1min to mix the coating liquid evenly, then immediately transfer it to a stoppered measuring cylinder, and add the paint suspension in the stoppered measuring cylinder to exactly 100ml; stopper the measuring cylinder, shake it vigorously again for more than 1min, let it stand on a non-vibrating table for 4h, read the volume of the sediment (accurate to 1ml), suspension rate = 1-(volume / 100ml)*100%, and take the average value of multiple groups of measurements at the same time.
[0129] High-temperature air permeability: Use a 6cm diameter 35-mesh round screen to immerse the prefabricated coating, drain so that the coating does not flow or transmit light, and put it in a drying oven to dry for one hour at 50°C. Put the sample prepared at room temperature into a high-temperature box-type resistance furnace. When the temperature in the furnace reaches 1200°C, keep the coating at this temperature for 10 minutes, cool it, and put it in a drying dish for use. Use a molding sand air permeability tester to test the air permeability. Place the sample on the sample tube and tighten it with bolts. Then use vaseline to seal the gap of the sample tube for measurement. Prepare three groups of samples for one coating and take the average value of the measurement.
[0130] Coating property: EPS foam 100*100*20mm 3Sample, immerse the foam sample completely into the paint at a uniform speed and then slowly take it out, repeat twice to ensure that the paint is evenly applied to the sample, place it vertically to avoid direct sunlight, and observe whether the sample is well coated with paint. According to experience, it is rated as excellent, good, and medium. Excellent: the coating surface is evenly attached without flow; Good: the coating surface has slight or partial sag and uneven thickness, but it does not affect the overall appearance quality; Medium: the coating surface has obvious sag, and the uneven thickness obviously affects the appearance quality.
[0131] High temperature crack resistance: 100*100mm 2 The flat corundum ceramic surface is coated with a coating of about 2mm. After the surface of the sample is dry, it is placed in a preheated 1200℃ high-temperature sintering furnace for 10 minutes. The sample is taken out to observe the cracks on the coating surface at high temperature, and four levels are determined: Ⅰ. Smooth without cracks or very fine cracks; Ⅱ. Dendritic or network cracks, with a crack width of less than 0.5mm; Ⅲ. Dendritic or network cracks, with a crack width of 0.5mm-1mm; Ⅳ. Dendritic or network cracks, with a crack width of more than 1mm.
[0132] Shedding and casting surface quality: After the casting cools down, remove the sand and coating, and visually observe the coating peeling, whether the casting surface is smooth, whether there is sand sticking, and the shape of the peeled coating.
[0133]
[0134] It can be seen from Table 8 and Examples 1 to 3 that as the proportion of aggregate increases, the proportion of binder to suspending agent decreases, which can improve air permeability but reduce the suspension rate, and has no obvious effect on coating properties and high-temperature crack resistance.
[0135] Comparative Examples 1 to 4 are based on Example 1, except that mica, quartz powder, magnesium oxide and white carbon are removed from the raw materials respectively, and the ratios of the other components are kept unchanged.
[0136] Comparative Example 1 removes the mica from the aggregate and keeps the ratio of bauxite to quartz powder unchanged. Compared with Example 1, the suspension of Comparative Example 1 is significantly reduced while the high-temperature permeability does not change much, the coating property is reduced, and after sintering, grade II cracks and sand sticking occur. This is because the flaky particles of the mica powder in Example 1 are arranged in parallel, overlapped and overlapped in the coating film to form a laminated structure, which increases the density of the coating film, thereby improving the strength of the coating film. Mica improves the suspension and coating properties of the coating in the casting coating; and although the flaky structure of mica can increase the hidden air pores for the coating, due to the increase in the amount of quartz powder in Comparative Example 1, the phase change and thermal expansion of quartz during sintering offset the reduced permeability effect caused by the lack of mica.
[0137] In Comparative Example 2, the quartz powder in the aggregate is removed and the ratio of bauxite to mica is kept unchanged. The suspension property of Comparative Example 2 does not change much, while the air permeability is significantly reduced. The coating property and high-temperature crack resistance remain almost unchanged, but the coating is not smoothly removed from the casting and there are defects such as sand sticking and pores on the surface of the casting. Example 1 contains quartz powder. When quartz is sintered at a high temperature of about 560°C, a solid phase transition will occur in which the dominant phase changes from the α phase to the β phase with a looser lattice. The air permeability of the aggregate will be greatly improved. At the same time, the aluminum oxide contained in the bauxite reacts with the silicon dioxide in the quartz powder at high temperature to form a low-melting point composite structure to promote the sintering of the aggregate. In Comparative Example 1, the quartz powder is removed, which seriously reduces the air permeability and sinterability of the aggregate. However, due to the increase in the mica content, the strength and crack resistance of the coating are also improved. However, due to the reduced sinterability and air permeability of the coating, the coating is difficult to peel off and the casting is Surface defects such as sand adhesion and pores.
[0138] In comparative example 3, magnesium oxide is removed from the binder and the ratio of anhydrous aluminum dihydrogen phosphate, white carbon black and ethylene glycol is kept unchanged. In comparative example 4, white carbon black is removed from the binder and the ratio of anhydrous aluminum dihydrogen phosphate, ethylene glycol and magnesium oxide is kept unchanged. As a new environmentally friendly and high temperature resistant adhesive, one of the defects of aluminum dihydrogen phosphate is that it is easy to shrink violently during sintering, resulting in a large film shrinkage rate, and the adhesive film is deformed and cracked. The magnesium oxide added in the present invention can partially react with aluminum dihydrogen phosphate at room temperature to form a three-dimensional network structure, thereby initially solidifying and improving the strength of the adhesive film at high temperature to reduce the tendency of deformation and rupture; the added white carbon black has good dispersibility, and can be used as a nucleation point for aluminum dihydrogen phosphate crystals during sintering to help crystal growth and promote film formation. It also serves as a filler to make up for the fine cracks caused by the shrinkage of aluminum dihydrogen phosphate during film formation. Similar to magnesium oxide, it can improve the sintering performance of the binder. In Comparative Examples 3 and 4, magnesium oxide and white carbon black were removed respectively, the coating was dry, and cracks were generated inside during sintering, which seriously reduced the strength and crack resistance of the coating. Some parts even deformed and collapsed under the scouring of the molten metal and the white film burning gas, resulting in surface defects such as unevenness and sand adhesion on the casting surface.
[0139] Therefore, the present invention effectively overcomes various shortcomings in the prior art and has high industrial utilization value.
[0140] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A coating for casting alloy steel lost foam, characterized in that: The invention comprises the following raw materials in parts by weight: 79-89 parts of aggregate, 3-7 parts of binder, 4-7 parts of suspending agent, 1.5-3 parts of surfactant, 1.5-2.5 parts of defoamer and 1-1.5 parts of preservative; wherein the aggregate, in terms of mass percentage, comprises 78-82wt% of bauxite, 12-15wt% of mica and 3-10wt% of quartz powder; The binder comprises, by weight percentage, 42-50 wt% of anhydrous aluminum dihydrogen phosphate, 18-25 wt% of white carbon black, 12-17 wt% of ethylene glycol and 8-28 wt% of magnesium oxide.
2. The coating for lost foam casting of alloy steel according to claim 1, characterized in that: The suspending agent comprises, by weight percentage, 35-50 wt% sodium carboxymethyl cellulose, 45-50 wt% sodium bentonite and 10-20 wt% sodium alginate; And / or, the surfactant is isomeric tridecanol polyoxyethylene ether; And / or, the defoaming agent is n-octanol; And / or, the preservative, in terms of mass percentage, comprises 25-50wt% potassium sorbate and 50-75wt% chitosan; And / or, the bauxite is 220-270 mesh high-alumina bauxite, and the Al2O3 content is greater than 85%; And / or, the mica is 250-270 mesh; And / or, the quartz powder is 180-220 mesh; And / or, the white carbon black is nano-scale white carbon black; And / or, the anhydrous aluminum dihydrogen phosphate, white carbon black and magnesium oxide are all powders.
3. The method for preparing the coating for lost foam casting of alloy steel according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Prepare sodium carboxymethyl cellulose suspension, sodium bentonite suspension and sodium alginate suspension according to the proportion of ingredients; S2. Mix and grind the aggregate, anhydrous aluminum dihydrogen phosphate, white carbon black and magnesium oxide according to the proportion of ingredients to obtain a mixed abrasive; S3, the three suspensions in step S1 are mixed to obtain a mixed suspension, the surfactant, defoamer, preservative and ethylene glycol are added to the mixed suspension in batches, and the obtained mixed solution is then added to the mixed abrasive obtained in step S2 in batches, and mixed evenly to obtain the coating for the lost foam of cast alloy steel.
4. The method for preparing the coating for lost foam casting of alloy steel according to claim 3, characterized in that: The concentration of the sodium carboxymethyl cellulose suspension in step S1 is 2-3 wt %; and / or, the concentration of the sodium bentonite suspension in step S1 is 1.5-2 wt %; And / or, the concentration of the sodium alginate suspension in step S1 is 1-1.5 wt %.
5. The method for preparing the coating for lost foam casting of alloy steel according to claim 3, characterized in that: The solvents of the sodium carboxymethyl cellulose suspension, the sodium bentonite suspension and the sodium alginate suspension in step S1 are all deionized water.
6. The method for preparing the coating for lost foam of alloy steel casting according to claim 5, characterized in that: The sodium carboxymethyl cellulose suspension, the sodium bentonite suspension and the sodium alginate suspension in step S1 are obtained by adding sodium carboxymethyl cellulose, sodium bentonite and sodium alginate into deionized water, respectively, mixing them into slurries and foaming them.
7. The method for preparing the coating for lost foam casting of alloy steel according to claim 3, characterized in that: The bauxite, mica and quartz powder in the aggregate in step S2 are kept at 200-230° C. for at least 30 minutes before mixing, and then cooled in a dry environment before mixing and grinding.
8. The method for preparing the coating for lost foam casting of alloy steel according to claim 7, characterized in that: The heat preservation is carried out in a high-temperature sintering furnace.
9. The method for preparing the coating for lost foam casting of alloy steel according to claim 3, characterized in that: The grinding in step S2 is carried out in a planetary ball mill, using zirconium oxide grinding balls with a diameter of 1.4-1.6 mm and a content of more than 90%, and grinding the mixed abrasive at a rotation speed of 300-330 rpm for 3-4 hours.
10. Use of the coating for lost foam casting of alloy steel according to any one of claims 1 to 2 in the field of lost foam casting of alloy steel.
Citation Information
Patent Citations
Coating for molds and expendable cores
CA1235254A
Corrosion resistant refractory coating
CA1237450A
Coating for lost foam casting, and preparation method thereof
CN103506566A
High-precision evanescent mode cast steel coating
CN104275435A
Thin-wall pipe evanescent mode paint and preparation method and application thereof
CN107052227A
Cited By
Special coating for lost foam of motor casing as well as preparation method and application of special coating
CN121423526A
Special coating for large machine tool casting lost foam as well as application and use method of special coating
CN121467614A
A special coating for large machine tool casting lost foam and its application and use method
CN121467614B